Improved Associated Task Scheduling in Different Heterogeneous systems: تحسين جدولة المهام المترابطة في الأنظمة مختلفة التجانس - Bassim Ali Oumran, Rowayda AAdel Muhbani (Journal of engineering sciences and information technology, 2021)
Scheduling of associated tasks in heterogeneous systems is very important to reduce the total completion time as heterogeneity and coherence introduce more complexity. Several studies have focused on studying task scheduling in homogeneous systems and some studies have been limited to scheduling in heterogeneous systems. In this paper, a new algorithm was created and a simulation of the proposed algorithm was designed and tested using a random schema generator. This algorithm showed better results than its predecessors in terms of schedule length ratio relative to heterogeneity factor and Communication to Computation Ratio factor.